Learning skills for healthy bodies and healthy lives: the school health policies trough political discourse - Riso, B. (Torino, 28-31 August 2013 - ESA 11th Conference: crisis, critique and change. Abstract book, 2013)
Although there is a small investment in health promotion and primary health care in Portugal we can observe a continuous development of school health policies addressing the requirements and orientations of the World Health Organization and European organisations. The political documents outline the school as an important place for learning health concepts and healthy practices, since childhood. This research seeks to know the dominant trends in management and political strategy regarding school health, considering the school as a social context where particular health policies take place. The aim was to provide some empirical evidence for understanding the ground and the scope of school health policies in Portugal. The governmental and political discourse widespread by policy documents that shape the school health was the starting point for this analysis, thus the choice of a qualitative method and the selection of documental analysis as the technique for data collection. The importance of science, namely the medical expertise, in policies elaboration and the medical discourse about health risks were recognized as central pillars of the discourse on health promotion in school. In addition, the emphasis on individual responsibility for health as an act of true citizenship seems to be recognized through the individual ability to manage life skills in order to conquer a healthy body and a healthy lifestyle. These were the main elements that emerged from this sociological reflection around the school health policy in Portugal.